Genomic variant in CAV1 increases susceptibility to coronary artery disease and myocardial infarction. (March 2016) - Chen, Shanshan; Wang, Xiaojing; Wang, Junhan; Zhao, Yuanyuan; Wang, Dan; Tan, Chengcheng; Fa, Jingjing; Zhang, Rongfeng; Wang, Fan; Xu, Chaoping; Huang, Yufeng; Li, Sisi; et al.
Abstract: Background: The CAV1 gene encodes caveolin-1 expressed in cell types relevant to atherosclerosis. Cav-1 -null mice showed a protective effect on atherosclerosis under the ApoE − / − background. However, it is unknown whether CAV1 is linked to CAD and MI in humans. In this study we analyzed a tagSNP for CAV1 in intron 2, rs3807989, for potential association with CAD. Methods and Results: We performed case–control association studies in three independent Chinese Han populations from GeneID, including 1249 CAD cases and 841 controls in Population I, 1260 cases and 833 controls in Population II and 790 cases and 1212 controls in Population III (a total of 3299 cases and 2886 controls). We identified significant association between rs3807989 and CAD in three independent populations and in the combined population ( P adj = 2.18 × 10 −5, OR = 1.19 for minor allele A). We also detected significant association between rs3807989 and MI ( P adj = 5.43 × 10 −5, OR = 1.23 for allele A). Allele A of SNP rs3807989 was also associated with a decreased level of LDL cholesterol. Although rs3807989 is a tagSNP for both CAV1 and nearby CAV2, allele A of SNP rs3807989 was associated with an increased expression level of CAV1 (both mRNA and protein), but not CAV2 . Conclusions: The data in this study demonstrated that rs3807989 at the CAV1 / CAV2 locus was associated with significant risk of CAD and MI by increasing expression of CAV1 (but not CAV2 ). Thus, CAV1 becomes a strong candidate susceptibility gene for CAD/MI in humans. Highlights: Identification of a new susceptibility gene ( CAV1 ) for CAD and MI. First demonstration of association between a genomic variant in CAV1 and CAD/MI. The minor allele A of CAV1 tagSNP rs3807989 increases risk of CAD and MI. Allele A of rs3807989 is associated with increased CAV1 expression, but not CAV2 expression.